2022
DOI: 10.1039/d1ra06981k
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of anticancer sulfonated indolo[2,1-a]isoquinoline and benzimidazo[2,1-a]isoquinolin-6(5H)-ones derivatives via a free radical cascade pathway

Abstract: A facile CuBr2 induced tandem radical reaction has been achieved, leading to sulfonated indole and benzimidazole derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A possible reaction mechanism is proposed on the basis of the above experimental observations and previous literature reports (Scheme 7). [4b–d,5] Initially, benzoate radical is formed by the thermal cleavage of BPO [6] . Then, the 1,3‐dioxolane is activated by the benzoate radical to generate radical A .…”
Section: Resultsmentioning
confidence: 99%
“…A possible reaction mechanism is proposed on the basis of the above experimental observations and previous literature reports (Scheme 7). [4b–d,5] Initially, benzoate radical is formed by the thermal cleavage of BPO [6] . Then, the 1,3‐dioxolane is activated by the benzoate radical to generate radical A .…”
Section: Resultsmentioning
confidence: 99%
“…Pan et al reported a one-step synthesis of benzimidazo[2,1- a ]isoquinolinone 79a and indolo[2,1- a ]isoquinoline 79b (Scheme 14). 58 The tert -butoxyl radical attacks the sulfonothiolate 77 to generate a sulfonyl radical that adds to alkene 76 generating radical intermediate 78 which on further cyclization and subsequent oxidation via SET following deprotonation affords the isoquinolinone derivative 79 . The anti-tumour activity of some representative isoquinoline skeletons was examined via the CCK8-assay of MCG-803, T-24 and HeLa tumour cell lines, where significant anti-tumour potential was exhibited by methoxy phenylsulfonyl benzo[4,5]imidazo[2,1- a ]isoquinolinone (IC 50 = 4 μM) against MCG-803 cell lines.…”
Section: Transition Metal-mediated Cascade Reactionsmentioning
confidence: 99%
“…Pan et al reported a one-step synthesis of benzimidazo[2,1-a] isoquinolinone 79a and indolo[2,1-a]isoquinoline 79b (Scheme 14). 58 The tert-butoxyl radical attacks the sulfonothiolate 77 to generate a sulfonyl radical that adds to alkene 76 generating radical intermediate 78 which on further cyclization and subsequent oxidation via SET following deprotonation affords the isoquinolinone derivative 79. The…”
Section: Radical Cascade Reactionsmentioning
confidence: 99%
“…Additionally, the synthesis of isoquinoline alkaloid moxaverine (gastrointestinal drug) under the optimized conditions was also carried out successfully. In 2022, Huang and coworkers [103] demonstrated an efficient synthesis of indolo[2,1-a]isoquinolines/ benzimidazo[2,1-a]isoquinolin-6(5H)-ones 193 via Cucatalyzed radical domino addition/cyclization reaction (Scheme 66). The activated alkenes 191 and substituted thiosulfonates 192 underwent a domino reaction using 10 mmol % CuBr 2 catalyst and 3 equiv.…”
Section: Copper Catalysismentioning
confidence: 99%
“…In 2022, Huang and coworkers [103] demonstrated an efficient synthesis of indolo[2,1‐ a ]isoquinolines/benzimidazo[2,1‐ a ]isoquinolin‐6(5 H )‐ones 193 via Cu‐catalyzed radical domino addition/cyclization reaction (Scheme 66). The activated alkenes 191 and substituted thiosulfonates 192 underwent a domino reaction using 10 mmol % CuBr 2 catalyst and 3 equiv.…”
Section: Metal‐catalyzed Synthesis Of Isoquinolinesmentioning
confidence: 99%